The exclusion of marriage unity as a case of marriage nullity in the bishop process - LESZCZYŃSKI, KS. GRZEGORZ (Prawo Kanoniczne, 2018)
Taking up the value of confessio iudicialis and the other proofs for declaring a marriage null and voit in the short bishop process, the author begins his reflections with a look at one of the marriage property that is marriage unity. From the point of view of marriage validity, of special significance is also the analysis of confessio iudicialis and testimonies in the Code of Canon Law from 1983. The last part of the author’s reflections is devoted to the analysis of judge presumptions and causes of simulation of marriage, according to Pope’s Francis Mitis Iudex Dominus Iesus.